Sociologie et religion dans la pensée de Gramsci - Lucas, Marie (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2019)
The rejection of sociology is a Leitmotiv of Gramsci’s writings. According to him, sociologyis abstract, naturalistic and dogmatic conception of knowledge that arose in the framework of the socialist positivism. However, Gramsci is not against any development within social sciences. Indeed, the philosophy of praxis aims to connect practice and theory in order to establish a successful political action. Given that, religion is an excellent example of the way in which Gramsci describes the political meaning of knowledge. The Catholic Church, in particular, embodies an ideology that is immanent and functional to an organised collectivity. Unlike positivists, Gramsci does not approach religion as the “empire of the irrational” but as the very essence of society. The political thought of the Prison Notebooks is based on an anti-deterministic interpretation of Marx, rather than on an anti-religious reading of Marxism. Religion is not suspicious as such; Gramsci is rather polemical against any theory that is not anchored into social life and that not represent, so to say, a political “translation” of it. Keywords: Sociology, Religion, Science, Ideology.